Prottoy Healing Sanctuary : psychiatry and de-addiction rehabilitation center Narsingdhi, Bangladesh - Showrab, Shahriaz Alam (BRAC University, 2019)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Architecture, 2018.